The treatment of oil palm empty fruit bunch fiber for subsequent use as substrate for cellulase production by aspergillus terreus suk-1 - Norhayati, Abu Bakar (2006)
Cellulases are important in industrial enzyme which is a main part in industrial process such as in bio-bleaching and bioethanol production. Nowadays, our country encourages the production of bioethanol from the biomass material such as oil palm empty fruit bunch fiber in order to enhance the resources of ethanol production and reduce the cost.In this project, oil palm empty fruit bunch fiber was used as a substrate for the production of cellulase enzyme by Aspergillus terreus SUK-1. In order to enhance the cellulase production, pretreatment on substrate are performed with different type of methods. Comparison results of cellulase enzyme production are determined between the substrate which is pretreated with acid and alkaline pretreatment. The effect of steam explosion on the substrate also was identified in shaking flask fermentation. From the experimental work, it was found that the highest xylanase and carboxymethylcellulase activity was in fermentation of acid treated substrate than alkali treated substrate and untreated substrate It also found that by autoclaved the substrate with chemicals produced the highest cellulase enzyme with value 0.167836U/ml for xylanase and 0.3534U/ml for carboxymethylcellulase.